Researching the creation of a national curriculum from systems to classrooms. (April 2013) - Gerrard, Jessica; Albright, James; Clarke, David J; Clarke, Doug M; Farrell, Lesley; Freebody, Peter; Sullivan, Peter
Under the auspices of its 'Education Revolution', the Federal Labor Government is currently implementing a national curriculum for schools. Representing an important intervention into educational practice and governance, the Australian Curriculum offers a unique research opportunity, providing substantial scope for the examination of the changing systems and school-level practices entailed in large-scale curriculum reform. Research into the Australian Curriculum also presents a valuable opportunity to develop educational research methodologies that attend to the complex and multifaceted processes of curriculum reform, from systems to classrooms. Taking two of the disciplinary towers of modern curricula (English and mathematics) and Australia's two largest jurisdictions (New South Wales and Victoria) as the focus, this article draws on a three-year Australian Research Council Linkage Project to outline an approach to researching major curriculum reform.